PRIME IDEAL ON SEMIRINGS D_nxn (Z^+) - Setyawati, Dian Winda (MATEMATIKA, 2011)
Let R be a semirings. A subset I of R is called an ideal of R if and then and I is called prime ideal if for then or On semirings , a non zero ideal I is prime if and only if , for p is prime or I = <2,3>. A paper will show form of prime ideal of semirings